Assessing food consumed away from home in low-and middle-income countries by developing specific modules for household surveys: Experimental evidence from Vietnam and Burkina Faso - Landais, Edwige; Pelloquin, Raphaël; Maître d’Hôtel, Elodie; Truong Tuyet, Mai; Hoang Thu, Nga; Bui Thi Thao, Yen; Do Thi Phuong, Ha; Thu, Trang Tran Thi; Somé, Jérôme; Bene, Christophe; Verger, Eric O. (2024)
In a world rapidly transitioning, food consumption away from home is rising, therefore representing an increasing share of individual’s diet. Food consumed away from home negatively impacts diet, nutritional status and consequently has detrimental effects on health. In some contexts, where individual level dietary intake surveys are not regularly conducted, this behavior is not well documented leading to a gap of knowledge. The aim of the present study was to develop and validate in Burkina Faso and Vietnam specific modules that could be added to Household Consumption and Expenditure Surveys that are usually regularly conducted worldwide, in order to document the economic and nutritional importance of food consumption away from home. In each country, two survey modules, one long (100 food items) and one short (30 food items) were developed, to measure individual-level food consumption away from home over the last 7 days. The modules were relatively validated in comparison with data from three non-consecutive 24-hour dietary recalls conducted over the same 7-days period. The validation was conducted in different settings (urban, peri-urban and rural) in Burkina Faso (n = 924) and Vietnam (n = 918). In both countries, a good concordance between the 24-hour dietary recalls and the modules in their ability to identify a person as having consumed food away from home (>77%) was found. However, in both countries, both modules underestimate the mean energy intake coming from foods consumed away from home (from 122 to 408 kcal) while they overestimate the budget allocated to it (from -0.07 to -0.29 USD/day). None of developed food away from home modules were considered as valid. There is a need for the international community to continue to work on developing and validating tools capable to estimate nutritional intakes related to food consumption away from home and that could be added to regular national household-level surveys.